Trust as a Mediator of the Effect of E-WOM on Repurchase Intention on the Itemku Site in Denpasar City - I Putu Krisna Meiyasa; I Gusti Agung Ketut Gede Suasana (International Journal of Economics, Business and Innovation Research, 2023)
The decreased repurchase intention on the Itemku site can be influenced by various factors, such as the lack of information received by customers or reduced customer trust. This study aims to analyze the effect of E-WOM on repurchase intention, the effect of E-WOM on trust, the effect of trust on repurchase intention, and the role of trust as a mediator of the effect of E-WOM on repurchase intention. This study had a sample of 100 Itemku site customers who were domiciled in Denpasar City. The data analysis technique used consisted of descriptive statistical analysis, path analysis, and sobel test. The results of the study show that E-WOM has a positive and significant effect on repurchase intention. E-WOM has a positive and significant effect on trust. Trust has a positive and significant effect on repurchase intention. Trust is able to partially mediate the effect of E-WOM on repurchase intention. This study contribute to the existing empirical evidence by further expanding our understanding of the role of trust as a mediator in the influence of E-WOM on repurchase intention. Practical implications make it useful for Itemku companies to be able to use this study as a learning reference.